If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
15*y = 5*(-1/5)+4 // - 5*(-1/5)+4
15*y-(5*(-1/5))-4 = 0
15*y-4+1 = 0
15*y-3 = 0 // + 3
15*y = 3 // : 15
y = 3/15
y = 1/5
y = 1/5
| 284-5x=40x+19 | | Y/3+7=12 | | 2(y-3)=-2 | | 4(y-2)=3(1.5+x) | | 6(t-5)+4t=5(2t+3)-12 | | 12(-4x+9)=16-2x | | 119=n-66 | | 15x-20(4/15+5/15x)=-7 | | -(8y+2)-(-7y-8)=3 | | 5y^3*3y^5= | | z=3+j | | 6x+7(4-x)=23 | | 2(7v-3)=22 | | t+27=15 | | y=x^5-2x^3+x-3 | | 4(2u-3)=24 | | (x-2)(x^2-4x+3)=0 | | log(2x+6)144=2 | | 4x+8+3x-5=129 | | 6(4-x)+7y=23 | | x^3+2x+8=0 | | x-3(9+x)=-11 | | x-3(9+x)=-11 | | 2(2x+3)-4(2-3x)=6+x | | 14-2(3p+p)=6(4+p) | | 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 | | -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= |